Islam sebagai sumber perundangan Malaysia - Mohd Kamal, Mohd Hisham (Dewan Bahasa dan Pustaka, 2007)
This work discusses the position of Islam as one of the sources of Malaysian law. It argues that Islam enjoys special position in the Federal Constitution and the State constitutions. Islamic law has the position and the potential to be an important source of Malaysian law.